PENGARUH INISIASI MENYUSU DINI TERHADAP PERUBAHAN SUHU TUBUH BAYI BARU LAHIR DI BPM â€œYâ€ KOTA BUKITTINGGI TAHUN 2013 - Yeltra Armi, Yeltra Armi; Evi Susanti, Evi (Jurnal Kesehatan - STIKes Prima Nusantara, 2013)
The majority of newborns are born normal and healthy, the baby does not require internention after delivery, in addition to dried with a towel warner and perform skin contact with their mothers. Data obtained from dr. Achmad Mochtar Hospital in 2013, obtained the data that the incidence of hypothermia as much as 1.7%, the newborn as much as 2.6%, and asphyxia as much as 4.9%. One handling the heat loss (Hypothermia), one of them with early breastfeeding initiation (IMD). This study aims to determine whether there is influence of early breastfeeding inititiation to the prevention of hypothermia in newborns in BPM â€œYâ€ cities bukittinggi 2013. This research type is a quantitative research design is quasi experimental. The sampling method accidental sampling. Data collected by observation and paired t-test is komputerisasi. From data processing is done, p value=0,0001. Can be explained statistically significant relationship between the effects of early breastfeeding initiation to the prevention of hypothermia in newborns. This study shows that there is an increase in temperature after IMD. Expected to midwife later to IMD in newborns to avoid hypothermia.